2021
DOI: 10.1021/jacs.1c04648
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective and Diastereodivergent Synthesis of Spiroindolenines via Chiral Phosphoric Acid-Catalyzed Cycloaddition

Abstract: A diastereodivergent and enantioselective synthesis of chiral spirocyclohexyl-indolenines with four contiguous stereogenic centers is achieved by a chiral phosphoric acid catalyzed cycloaddition of 2-susbtituted 3-indolylmethanols with 1,3-dienecarbamates. Modular access to two different diastereoisomers with high enantioselectivities was obtained by careful choice of reaction conditions. Their functional group manipulation provides an efficient access to enantioenriched spirocyclohexyl-indolines and -oxindole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 91 publications
0
17
0
Order By: Relevance
“…Indeed, the Masson group nicely showed that 2-alkylindole-3-carbinols 61 , upon activation with a chiral phosphoric acid and reaction with dienecarbamates 59 at low temperature, furnished spirocyclohexyl indolenines 62 with good yields and excellent enantio- and dia­stereoselectivities across a broad substrate range (Scheme 18 ). 43 Interestingly, at elevated temperature, a different dia­stereomer 63 was formed exclusively with full retention of enantioselectivity, suggesting that a thermodynamic equilibration occurred at elevated temperature via a retro-Friedel–Crafts reaction. On the other hand, at low temperature, the kinetically preferred stereoisomer had likely been formed.…”
Section: Cycloadditions Of Indolyl-3-methidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, the Masson group nicely showed that 2-alkylindole-3-carbinols 61 , upon activation with a chiral phosphoric acid and reaction with dienecarbamates 59 at low temperature, furnished spirocyclohexyl indolenines 62 with good yields and excellent enantio- and dia­stereoselectivities across a broad substrate range (Scheme 18 ). 43 Interestingly, at elevated temperature, a different dia­stereomer 63 was formed exclusively with full retention of enantioselectivity, suggesting that a thermodynamic equilibration occurred at elevated temperature via a retro-Friedel–Crafts reaction. On the other hand, at low temperature, the kinetically preferred stereoisomer had likely been formed.…”
Section: Cycloadditions Of Indolyl-3-methidesmentioning
confidence: 98%
“…Scheme18 [2+4]-Cycloadditions of 2-alkylindole-3-carbinols 61 with 1-amino-substituted 1,3-butadienes 5943 …”
mentioning
confidence: 99%
“…As such, Bernardi et al reported the use of simple unsubstituted dienecarbamates [12] in Povarov reaction leading to the synthesis of 1,2,3,4-tetrahydroquinolines (Scheme 1b, right). [13] In continuation of our research program in catalytic asymmetric reactions with dienecarbamates, [14] we decided to explore their reactivities in connection with 2-benzothiazolimines. Indeed, these imines are versatile synthetic intermediates used for the syntheses of various heterocycles [15] and they have been embedded in direct catalytic asymmetric annulation strategies.…”
Section: Tetrahydropyridinesmentioning
confidence: 99%
“…[47] By using 10 mol% of TRIP catalyst (S-Cat. 8), an array of enecarbamates (57) with substitutions in para-, meta-and ortho-position of the aryl group of the olefin were included in this annulation reaction and the corresponding 2,3,4-trisubstituted chroman products (58) were obtained in high yields with high enantioselectivities and diastereoselectivities (Scheme 17). In addition, a range of o-hydroxybenzyl alcohols (56) with variations of both the quinone methide fragment and the β-aryl substituent could be used in this reaction to generate chroman products bearing three stereogenic centers and could therefore be used in natural product synthesis.…”
Section: Stereoselective [4 + 2] Cycloaddition and Annulation Reactionsmentioning
confidence: 99%
“…In 2021, Masson and co-workers established the chiral phosphoric acid catalyzed diastereodivergent and enantioselective construction of chiral spirocyclohexyl-indolenines (82). [58] The vinylindoliniminium ion (In- center, with excellent enantioselectivities and diastereoselectivities. By carefully selecting reaction conditions, the authors obtain two distinct diastereoisomers with high enantioselectivities (Scheme 25).…”
Section: Stereoselective [4 + 2] Cycloaddition and Annulation Reactionsmentioning
confidence: 99%